The right hemisphere’s contribution to discourse processing: A study in temporal lobe epilepsy - Lomlomdjian, Ana Carolina (2017)
Objective: Discourse skills - in which the right hemisphere has an important role - enables verbal communication by selecting contextually relevant information and integrating it coherently to infer the correct meaning. However, language research in epilepsy has focused on single word analysis related mainly to left hemisphere processing. The purpose of this study was to investigate discourse abilities in patients with right lateralized medial temporal lobe epilepsy (RTLE) by comparing their performance to that of patients with left temporal lobe epilepsy (LTLE). Methods: 74 pharmacoresistant temporal lobe epilepsy (TLE) patients were evaluated: 34 with RTLE and 40 with LTLE. Subjects underwent a battery of tests that measure comprehension and production of conversational and narrative discourse. Disease related variables and general neuropsychological data were evaluated. Results: The RTLE group presented deficits in interictal conversational and narrative discourse, with a disintegrated speech, lack of categorization and misinterpretation of social meaning. LTLE group, on the other hand, showed a tendency to lower performance in logical-temporal sequencing. Significance: RTLE patients showed discourse deficits which have been described in right hemisphere damaged patients due to other etiologies. Medial and anterior temporal lobe structures appear to link semantic, world knowledge, and social cognition associated areas to construct a contextually related coherent meaning.